2017
DOI: 10.26773/mjssm.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Common Running Overuse Injuries and Prevention

Abstract: Runners are particularly prone to developing overuse injuries. Th e most common runningrelated injuries include medial tibial stress syndrome, Achilles tendinopathy, plantar fasciitis, patellar tendinopathy, iliotibial band syndrome, tibial stress fractures, and patellofemoral pain syndrome. Two of the most signifi cant risk factors appear to be injury history and weekly distance. Several trials have successfully identifi ed biomechanical risk factors for specifi c injuries, with increased ground reaction forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
(60 reference statements)
0
9
0
2
Order By: Relevance
“…Th e themes of sports medicine published in the MJSSM are: "Evaluation of Behavior to Pain Measures in Athletes -A Correlative Analysis" (Kumar, Sandhu, & Shenoy, 2013), "Osgood Schlatter's disease -A burst in young football players" (Domingues, 2013), "Overuse Knee Injuries in Athletes" (Kezunovic, 2013), "Th eoretical Issues and Methodological Implications in Searching Visual Search Behaviours: A Preliminary Study Comparing the Cognitive and Ecologic Paradigms" (Afonso, 2013), "Perceived Muscle Soreness, Functional Performance and Cardiovascular Responses to an Acute Bout of Two Plyometric Exercises" (Arazi, Asadi, & Chegini, 2016), "Common Injuries of Picture 1. Journal's web page Collegiate Tennis Players (Valleser & Narvasa, 2017) and "Common Running Overuse Injuries and Prevention" (Kozinc & Sarabon, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Th e themes of sports medicine published in the MJSSM are: "Evaluation of Behavior to Pain Measures in Athletes -A Correlative Analysis" (Kumar, Sandhu, & Shenoy, 2013), "Osgood Schlatter's disease -A burst in young football players" (Domingues, 2013), "Overuse Knee Injuries in Athletes" (Kezunovic, 2013), "Th eoretical Issues and Methodological Implications in Searching Visual Search Behaviours: A Preliminary Study Comparing the Cognitive and Ecologic Paradigms" (Afonso, 2013), "Perceived Muscle Soreness, Functional Performance and Cardiovascular Responses to an Acute Bout of Two Plyometric Exercises" (Arazi, Asadi, & Chegini, 2016), "Common Injuries of Picture 1. Journal's web page Collegiate Tennis Players (Valleser & Narvasa, 2017) and "Common Running Overuse Injuries and Prevention" (Kozinc & Sarabon, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…This may be the cause of some overuse running injuries that are more prevalent in females because time to maximum rearfoot eversion has often been linked to overuse running injuries (Ferber, et al, 2009). Women are more prone to tibial stress syndrome and tibial stress fractures (Fernández & Rojano, 2020;Kozinc & Šarabon, 2017;Taunton, et al, 2002) and Becker et al (2017) and Fernández and Rojano (2020) suggest that eversion later in stance may be one of the biomechanical factors related to this type of injury risk. Sakaguchi et al (2014) also found a later occurrence of peak eversion in female runners but the differences between males and females were not significant and effect sizes were small.…”
Section: Discussionmentioning
confidence: 99%
“…Entre los efectos ecológicos más significativos podemos destacar la fragmentación de los ecosistemas, dispersión de especies exóticas y disminución de las poblaciones de especies de fauna y flora, producción de ruido y contaminación de las aguas y suelo (1). El atropellamiento de fauna es uno de los efectos más relevantes para el ecosistema ya que es común encontrar en las carreteras animales atropellados poli traumatizados que se desplazan y mueren en otro lugar sin poder registrar la muerte del animal (8).…”
Section: Discussionunclassified
“…En un estudio realizado en el Departamento de Sucre, Colombia encontraron que de un total de 431 animales muertos por atropellamiento, el 28.1% (121 animales) eran mamíferos, a su vez, el 6.1% (26 animales) pertenecían a la especie Didelphis marsupialis (8). A nivel de departamentos como Antioquia se relaciona con una alta mortalidad debido a colisiones; en países como Brasil y Venezuela es la especie más afectada por atropellamiento (9).…”
Section: Introductionunclassified